Pengaruh Media Powtoon terhadap Kemampuan Membaca Puisi Siswa Kelas 4 SDN 3 Dermolo Jepara - Wahyu Viky Dwi Indrawan; Muhammad Misbahul Munir; Dwiana Asih Wiranti (Universitas Ngudi Waluyo, 2026)
This study aims to analyze the effect of using powtoon media on the poetry reading ability of fourth-grade students at SDN 3 Dermolo Jepara. The main problem underlying this study is the low level of students’ poetry reading skills, indicated by limited mastery of pronunciation, intonation, expression, pauses, and appreciation, resulting from monotonous instruction and minimal use of interactive media. The study employed a quantitative approach with a One Group Pretest-Posttest design. The research subjects consisted of 24 fourth-grade students. Data were collected using a poetry reading performance rubric. Data analysis was carried out using descriptive statistics, Paired Sample T-test, and simple regression. The results showed that the mean pretest score was 68.54 and increased to 82,63 in the posttest. The hypothesis test yielded a significance value of 0,000, indicating a significant effect of powtoon media on students’ poetry reading ability. Powtoon media helps students understand reading techniques and is effective as an alternative learning medium for Indonesian language instruction in elementary schools. Abstrak Penelitian ini bertujuan menganalisis pengaruh penggunaan media Powtoon terhadap kemampuan membaca puisi siswa kelas 4 SDN 3 Dermolo Jepara. Permasalahan utama yang melatarbelakangi penelitian ini adalah rendahnya kemampuan membaca puisi siswa yang ditandai oleh kurangnya penguasaan lafal, intonasi, ekspresi, jeda, serta penghayatan akibat pembelajaran yang bersifat monoton dan minim pemanfaatan media interaktif. Penelitian menggunakan pendekatan kuantitatif dengan desain One Group Pretest–Posttest. Sampel penelitian terdiri atas 24 siswa kelas 4. Instrumen pengumpulan data berupa rubrik praktik membaca puisi. Analisis data dilakukan dengan statistik deskriptif, uji Paired Sample T-test, dan regresi sederhana. Hasil penelitian menunjukkan nilai rata-rata pretest sebesar 68,54 dan meningkat menjadi 82,63 pada posttest. Hasil uji hipotesis menunjukkan nilai signifikansi 0,000 yang menandakan adanya pengaruh signifikan penggunaan media powtoon terhadap kemampuan membaca puisi siswa. Media powtoon membantu siswa memahami teknik pembacaan dan efektif digunakan sebagai alternatif pembelajaran Bahasa Indonesia di sekolah dasar.